Wpływ COVID-19 na wykonywanie zadań publicznych z zakresu oświaty - Biały, Sebastian (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
Pandemic COVID-19 caused significant changes in the functioning of many economic industries but also human life itself. During global crisis times, the public administration should keep the continuity and stability of their activities, and in many cases adapt to the needs of citizens. Pandemic also affected the unit of the education system, changing the way of teaching from traditional to e-learning. Numerous government projects have tried to guarantee equal access to learning in these severe times using techniques and methods of distance learning. The author also sets out results from two examinations organized by the Central Examination Commission, from which it follows whether the so-called e-learning has significantly influenced science results.
Keywords: public tasks; educational law; COVID-19; e-learning; public administration